Carob (Ceratonia siliqua L.) Seed Constituents: A Comprehensive Review of Composition, Chemical Profile, and Diverse Applications - Salah Laaraj; Souad Salmaoui; Mohamed Addi; Chaimae El-rhouttais; Aziz Tikent; Amine Elbouzidi; Mohamed Taibi; Christophe Hano; Younes Noutfia; Kaoutar Elfazazi (Journal of Food Quality, 2023)
Carob (Ceratonia siliqua L.) is a tree species native to the Mediterranean region and belongs to the Fabaceae family. The tree is well-known for its sweet and nutritious fruits, which have been used for long time as a nutritious food. In addition to the edible fruits, the carob tree also produces seeds that are highly prized for their ability to produce carob gum (locust bean gum). The carob seed consists of three main components: the shell, the endosperm, and the embryo. The shell is the outermost layer of the seed, followed by the endosperm, which is the largest part of the seed and contains high levels of carbohydrates and proteins. The embryo is the smallest part of the seed and is rich on bioactive compounds. Carob seed constituents have attracted considerable attention due to their exceptional nutritional and therapeutic properties in various industries, including food, medicine, pharmaceuticals, cosmetics, and textiles. The high content of bioactive compounds in carob seeds, such as polyphenols, tannins, and flavonoids, is believed to be responsible for their antioxidant and anti-inflammatory properties. The use of carob seed constituents in the food industry is mainly due to their ability to act as thickeners and stabilizers in various foods. They are used as a substitute for other thickening agents such as guar gum and carrageenan, due to their superior properties. In the pharmaceutical industry, carob seeds have been found to have antidiabetic, antihyperlipidemic, and anticancer properties, among others. The cosmetics industry is also interested in the ingredients of carob seed, as they can improve hydration and elasticity of the skin. They are also used as a natural alternative to synthetic thickeners in cosmetic formulations. The textile industry has also recognized the potential of carob seed constituents, as they can be used as a natural dye and as a sizing agent to improve the strength and durability of textiles. In summary, carob seed constituents offer a wide range of applications in various industries, owing to their high content of bioactive compounds, excellent nutritional and therapeutic profile, and ability to act as thickeners, stabilizers, and antioxidants. This review has highlighted the latest findings on the chemical composition, applications, and health benefits of carob seed constituents.